Roadmap to Reasoning in Microservice Systems: A Rapid Review - Amr S. Abdelfattah; Tomas Cerny (Applied Sciences, 2023)
Understanding software systems written by others is often challenging. When we want to assess systems to reason about them, i.e., to understand dependencies, analyze evolution trade-offs, or to verify conformance to the original blueprint, we must invest broad efforts. This becomes difficult when considering decentralized systems. Microservice-based systems are mainstream these days; however, to observe, understand, and manage these systems and their properties, we are missing fundamental tools that would derive various simplified system abstract perspectives. Microservices architecture characteristics yield many advantages to system operation; however, they bring challenges to their development and deployment lifecycles. Microservices urge a system-centric perspective to better reason about the system evolution and its quality attributes. This process review paper considers the current system analysis approaches and their possible alignment with automated system assessment or with human-centered approaches. We outline the necessary steps to accomplish holistic reasoning in decentralized microservice systems. As a contribution, we provide a roadmap for analysis and reasoning in microservice-based systems and suggest that various process phases can be decoupled through the introduction of system intermediate representation as the trajectory to provide various system-centered perspectives to analyze various system aspects. Furthermore, we cover different technical-based reasoning strategies and metrics in addition to the human-centered reasoning addressed through alternative visualization approaches. Finally, a system evolution is discussed from the perspective of such a reasoning process to illustrate the impact analysis evaluation over system changes.